The debt-growth nexus in poor countries: a reassessment - Andrea F. Presbitero (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
This paper investigates the relationship between external indebtedness and economic growth, with a particular attention to LICs, for which the theoretical arguments of debt overhang and liquidity constraint have to be reconsidered. The estimation of a growth model, with a panel of 121 developing countries, supports a negative and linear relationship between past values of the NPV of external public debt and current economic growth. This is due to the ?extended debt overhang?, according to which a large indebtedness leads to misallocation of capital and discourage long-term investment and structural reforms. This work underlines the critical role of economic policies and institutions, the necessity of focusing on LICs and fostering macroeconomic stability.
Keywords: O11; C33; F34; H63; 330; External Debt; HIPC; Debt Relief; Economic Growth